THE USE OF AUDIO VISUAL MEDIA TO IMPROVE THE LEARNING OUTCOMES OF CLASS III STUDENTS OF SD INPRES BAROMBONG 1 MAKASSAR CITY - Raodatul Jannah; Nursamsilis Lutfin (Teaching English as a Foreign Language Overseas Journal, 2022)
The aim of the research was to improve the learning outcomes of third grade students at SD Impres Barombong I through the use of audio-visual media. The focus of this research was all grade III students of SD Inpres Barombong 1. This research lasted two cycles, each cycle was carried out for four meetings, the first to third meetings were the learning process and the fourth meeting was evaluation. Collecting data with observation techniques and giving tests, while the data analysis techniques used are quantitative and qualitative. Giving assignments with indicators at the reflection stage of the research cycle. The results achieved were (1) increased student reading learning outcomes, namely cycle I was in the sufficient category because there were 10 students or 47.61% who did not meet the minimum completeness criteria and cycle II was in the good category because there were only 5 students or 23 .81% of the 21 students who cannot meet the minimum completeness criteria, this will be continued by the class III teacher at SD Inpres Barombong 1 Makassar City. (2) there is an increase in student learning activities during learning takes place. Based on this research, it can be concluded that one way to improve reading learning outcomes is to use audio-visual media. Based on the results of the research above, it can be concluded that through the use of audio-visual media in class III students of SD Inpres Barombong 1 Makassar City experienced an increase in reading learning outcomes